Scene Synchronization in Close Coupled World Representations using SCIVE - Latoschik, Marc Erich; Froehlich, Christian; Wendler, Alexander (International Journal of Virtual Reality, 2006)
This paper introduces SCIVE, a Simulation Core for Intelligent Virtual Environments. SCIVE provides a Knowledge Representation Layer (KRL) as a central organizing structure. Based on a semantic net, it ties together the data representations of the various simulation modules, e.g., for graphics, physics, audio, haptics or Artificial Intelligence (AI) representations. SCIVE’s open architecture allows a seamless integration and modification of these modules. Their data synchronization is widely customizable to support extensibility and maintainability. Synchronization can be controlled through filters which in turn can be instantiated and parametrized by any of the modules, e.g., the AI component can be used to change an object’s behavior to be controlled by the physics instead of the interaction- or a keyframe-module. This bidirectional inter- module access is mapped by, and routed through, the KRL which semantically reflects all objects or entities the simulation comprises. Hence, SCIVE allows extensive application design and customization from low-level core logic, module configuration and flow control, to the simulated scene, all on a high-level unified representation layer while it supports well known development paradigms commonly found in Virtual Reality applications